2004
DOI: 10.1121/1.1778838
|View full text |Cite
|
Sign up to set email alerts
|

Auditory discontinuities interact with categorization: Implications for speech perception

Abstract: Behavioral experiments with infants, adults, and nonhuman animals converge with neurophysiological findings to suggest that there is a discontinuity in auditory processing of stimulus components differing in onset time by about 20 ms. This discontinuity has been implicated as a basis for boundaries between speech categories distinguished by voice onset time ͑VOT͒. Here, it is investigated how this discontinuity interacts with the learning of novel perceptual categories. Adult listeners were trained to categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
6
51
2
Order By: Relevance
“…However, subjects in the Pisoni et al (1982) experiment were asked to learn a different category boundary location, one that may be easier to learn than that used in the present experiment due to the location of regions of heightened psychoacoustic sensitivity (cf. discussion by Holt, Lotto, & Diehl, 2004).…”
Section: Generalizationmentioning
confidence: 96%
“…However, subjects in the Pisoni et al (1982) experiment were asked to learn a different category boundary location, one that may be easier to learn than that used in the present experiment due to the location of regions of heightened psychoacoustic sensitivity (cf. discussion by Holt, Lotto, & Diehl, 2004).…”
Section: Generalizationmentioning
confidence: 96%
“…The experiment used methods from auditory categorylearning experiments ͑e.g., Holt et al, 2004;Mirman et al, 2004͒ whereby distributions of sounds drawn from a twodimensional acoustic space were sampled in stimulus presentation. Listeners labeled the sound and received feedback to learn to assign category labels during training.…”
Section: Stimulimentioning
confidence: 99%
“…Holt, Lotto, & Kluender, 2001;Hauser, Newport, & Aslin, 2001). Likewise, training human adults to categorize complex nonspeech acoustic stimuli that model some of the complexity of speech stimuli has demonstrated that there are important perceptual (Holt, Lotto, & Diehl, 2004) and cognitive (Holt & Lotto, 2006) constraints on auditory learning that extend to speech categorization. Considering speech perception from a general cognitive-science perspective, it also becomes possible to integrate findings from visual categorization into theories of speech.…”
Section: Speech and Experiencementioning
confidence: 99%